The effectiveness of role-playing and active discussion strategies in the achievement of fifth-grade female students of scientific concepts (Journal of the College of Basic Education, 2022)
The research aims to identify the effectiveness of the strategies of role-playing and active discussion in the achievement of the fifth grade students of the scientific concepts.The research was limited to fifth grade female students in one of the schools affiliated to the Directorate of Education of Baghdad Al-Rusafa / 1, if the research sample was intentionally chosen from the Iraq Al-Khair School for Girls because it contains three classes for the fifth grade, and the three classes were chosen randomly, and the three research groups were rewarded in the variables (intelligence Previous achievement, previous information in science, chronological age